Synergetic Effect Of Rhizobium Sp. And Piriformospora Indica On Bioenhancing Activity, Symbiotic Parameters And Grain Yield In Pigeon Pea (Cajanus Cajan L.) (Applied Biological Research, 2016)
The synergetic effect of Rhizobium sp. (Cajanus) and Piriformospora indica on bioenhancing activity, symbiotic parameters and grain yield of pigeon pea  was evaluated. Nine genotypes were raised during kharif, 2013 at the  Experimental Farm, HAU, Hisar (India). Rhizobium sp. and P. indica, alone  or co-inoculated, along with untreated control were assessed for response of  genotypes to these organisms on various metric traits. Significant differences  among the genotypes for the studied traits indicated beneficial effect of both  the organisms. Among the treatments, P. indica inoculation alone was most  effective for most of the characters followed by dual inoculation of P. indica and Rhizobium. But for symbiotic traits the performance of Rhizobium alone  was better than dual inoculation or P. indica alone. The genotypes Manak,  Paras, UPAS 120, Pusa 991 and AH09-47 performed better with respect to  symbiotic, growth and yield parameters. Hence, these genotypes could be  used as parents in hybridization programme for genetic improvement of  pigeon pea
Keywords: Cajanus cajan; pigeon pea; Piriformospora indica; Rhizobium sp.; symbiosis